Is mannose‐binding lectin serum concentration a reliable predictor for recurrent vulvovaginal candidiasis?. Issue 2 (18th December 2018) - Ghazanfari, Mona; Falahati, Mehraban; Fattahi, Azam; Bazrafshan, Fatemeh; Nami, Sanam; Hosseinzadeh, Morteza; Heydarikohan, Fariba; Ghelman, Mohsen; Khoshmirsafa, Majid; Farzanegan, Ali
Summary: Recurrent vulvovaginal candidiasis (RVVC) is a common opportunistic, mucosal fungal infection, predominantly caused by the fungus Candida albicans . Mannose‐binding lectin (MBL) is an acute‐phase protein that plays a key role in the innate immunity defence against infectious disease. This study was conducted to evaluate the relationship between the MBL serum level and the relative expression of MBL mRNA in RVVC using real‐time PCR for the first time. The case‐control study included 40 female participants suffering from RVVC and 40 healthy individuals. The MBL serum level was measured using a commercial ELISA kit. The relative mRNA expression of the MBL gene was quantified using real‐time PCR. Data analysis was carried out byspss software. The MBL concentration was significantly higher in the participants suffering from RVVC compared to the control group (0.330 ng/mL vs 0.253 ng/mL). The prognostic value ( P  <   .001) for RVVC diagnosis has been calculated. Quantitative RT‐PCR results from 35 samples showed a low to significant values for mRNA levels corresponding to MBL gene expression (1‐352 folds) ( P  <   .001). The results of this study suggest that MBL plays a main role in the innate immunity and it is also affected by environmental factors and other genetic variations. Therefore, the MBL gene expression profile does not reflect precise phenotypic levels in the serum.